Energy Efficiency in Green Buildings: Indian Concept - Singh, Avtar (International Journal For Research In Mechanical & Civil Engineering, 2017)
Climate change, caused by the release of greenhouse gases (mainly carbon dioxide) into the atmosphere, has been recognized as one of the greatest threats of the 21st century. Share of energy consumption in India and China has also been on the raise due to sharp urbanization, population explosion, and intensive growth of IT and related business. Buildings are the dominant energy consumers in modern cities account upto 40% energy consumption. Their consumption can be largely cut back through improving efficiency, which is an effective means to lessen greenhouse gas emissions and slow down depletion of non- renewable energy resources. There is over 50% saving potential in the building sector and thus it is considered as a potential sector to meet the challenges of global energy and climate change. Along with introduction of energy efficiency measures, more effective means are needed to induce or compel greater efforts, especially to the signatories to the Kyoto Protocol. This technical paper discusses the role of energy efficiency in green buildings in Indian scenario to reduce the energy consumption and environmental degradation through Green House Gas emission (GHG). The possibility and benefits of harmonizing governmental and private-sector schemes are also discussed.